2003
DOI: 10.1889/1.1832553
|View full text |Cite
|
Sign up to set email alerts
|

52.5L: Late‐News Paper: Versatile Evaporation Source for Large OLED Panel Manufacturing

Abstract: We have developed an innovative and scalable evaporation source with a multi‐apertured injector manifold for uniform OLED material production over large area, non‐rotating panels. The source is integrated with optical monitoring for high precision and instantaneous flux adjustment using a valving mechanism. The modular design allows flexible deposition configurations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…42 This result was achieved using five ultrathin layers (mostly 10 nm) of evaporated molecules. Even with the advanced deposition tools coming on the market, [43][44][45] it will be challenging to maintain thickness control and defect levels in such thin films, especially at high speed.…”
Section: Light-emitting Diodesmentioning
confidence: 99%
“…42 This result was achieved using five ultrathin layers (mostly 10 nm) of evaporated molecules. Even with the advanced deposition tools coming on the market, [43][44][45] it will be challenging to maintain thickness control and defect levels in such thin films, especially at high speed.…”
Section: Light-emitting Diodesmentioning
confidence: 99%
“…Results We have investigated the performance of this valved source with a number of host and dopant materials, and showed that it can handle different materials with equal ease. In Figure 4 The flux rate can be monitored by either quartz crystal sensor or optical interferometry technique 4 . The sensor output can be used as feedback for stable rate control.…”
mentioning
confidence: 99%